Supercritical carbon dioxide extraction of essential oils from leaves of Eucalyptus globulus L., their analysis and application. Issue 6 (21st January 2016) - Singh, Aarti; Ahmad, Anees; Bushra, Rani
Abstract : A comparative study on the extraction of essential oil from the leaves of Eucalyptus globulus was conducted using traditional methods such as hydrodistillation (HD), solvent extraction (SE), ultrasonic-assisted extraction (UAE) and an innovative supercritical carbon dioxide (SC-CO2 ) extraction technique. Abstract : A comparative study on the extraction of essential oil from the leaves of Eucalyptus globulus was conducted using traditional methods such as hydrodistillation (HD), solvent extraction (SE), ultrasonic-assisted extraction (UAE) and an innovative supercritical carbon dioxide (SC-CO2 ) extraction technique. Each oil was evaluated by HPTLC (high performance thin layer liquid chromatography) and FTIR (Fourier transform infrared spectroscopy) fingerprinting with qualitative and semi-quantitative composition of the isolated essential oil determined by gas chromatography-mass spectrometry (GC-MS). The yield of essential oil was found to be 2.0%, 2.2%, 2.6% and 3.6% v/w, via HD, SE, UAE and SC-CO2, respectively. A total of 53 compounds were identified by GC-MS. Comparative studies have shown that the SC-CO2 technique is favourable for the extraction of monoterpene, sesquiterpene and oxygenated sesquiterpene hydrocarbons. HD, SE and US techniques are also important in the extraction of aliphatic saturated hydrocarbons, organic acids and esters. The maximum separation of compounds was observed at 254 nm by HPTLC fingerprinting. The present research paper covers different extraction methods, which may lead to different yields of essential oils; this further shows that the choice of the appropriate extraction method is very important to obtain the desired components in high yields with improved physiological activities. IC50 (Inhibition Concentration) values of E. globulus oil sample were found to be 47.61 and 26.05 μg mL −1 via DPPH and superoxide scavenging methods, respectively.